Pembuatan Video Promosi Menggunakan Adobe Premiere untuk Meningkatkan Engagement di Instagram Toko Thrift Baju Defiant Kabupaten Blitar - Muhammad Jauhar Annas Daud; Ahmad Fauzi; Umi Khabibah (INDO PUBLISHING, 2026)
Defiant Thrift Store is a secondhand-clothing store in Blitar Regency that has relied on Instagram as its main promotional channel, yet its video content has not been planned systematically, resulting in low audience engagement and limited brand awareness. This study aims to design a promotional video using the Adobe Premiere application as a digital promotional medium for Instagram Reels and to measure its effectiveness in increasing audience engagement on the Instagram account of Defiant Thrift Store. This study used the action research method comprising four stages: planning, action, observation, and reflection. Primary data were obtained through observation, interviews, and questionnaires distributed to 20 respondents consisting of the business owner, employees, computer experts, marketing experts, and consumers, while secondary data were obtained from Instagram Insight. The effectiveness of the video was measured using the EPIC Model (Empathy, Persuasion, Impact, Communication) and the Customer Response Index (CRI), while audience engagement was measured through Engagement Rate by Reach (ERR) and Engagement Rate by Impression (ERI). The results show that the EPIC Rate reached 4.10, categorized as effective, while the CRI score reached 63.9%, categorized as fairly effective. Instagram Insight data recorded an increase in account reach by 96.28% to 1,268 accounts, impressions by 96.93% to 3,653 views, and interactions by 62.22% to 78 interactions, with ERR of 5.83% and ERI of 2.14%. This study concludes that the promotional video produced through Adobe Premiere is effective in increasing engagement on the Instagram account of Defiant Thrift Store, so that consistency in visual identity and content planning needs to be maintained sustainably.